Multiple Impinging Jet Cooling of a Wavy Surface by Using Double Porous Fins under Non-Uniform Magnetic Field - Lioua Kolsi; Fatih Selimefendigil; Kaouther Ghachem; Talal Alqahtani; Salem Algarni (Mathematics, 2022)
Coupled effects of double porous fins and inhomogeneous magnetic field on the cooling performance of multiple nanojet impingement for a corrugated surface were numerically analyzed. Different values of magnetic field parameters (strength, inclination, and amplitude of spatially varying part) and double porous fin parameters (inclination and permeability) were used, while finite element method is used as the solution method. When parametric computational fluid dynamics (CFD) simulations were performed, there were 162.5% and 34% Nusselt number (Nu) enhancement with magnetic field for flat and wavy surfaces, respectively. The variations of average Nu became <semantics>36%</semantics> and <semantics>24%</semantics> when varying the inclination and amplitude of inhomogeneous magnetic for a flat surface, while the amounts were <semantics>43.7%</semantics> and <semantics>32%</semantics> for a corrugated one. The vortex distribution in between the jets and cooling performance was affected by the variation of double porous fin permeability and inclination. An optimization method was used for the highest cooling performance, while the optimum set of parameters was obtained at (Ha, Amp, Da, <semantics>Ω</semantics>) = (0.224, 0.5835, <semantics>7.59×10−4</semantics>, 0.1617). By using the double porous fins and inhomogeneous magnetic field, excellent control of the cooling performance of multiple impinging jet was obtained.